Femtosecond X-ray diffraction from twodimensional protein crystals. (2014) - Frank, M.; Carlson, D. B.; Hunter, M. S.; Williams, G. J.; Messerschmidt, M.; Zatsepin, N. A.; Barty, A.; Benner, W. H.; Chu, K.; Graf, A. T.; Hau-Riege, S. P.; Kirian, R. A.; et al.
No abstract available